MANAGEMENT INFORMATION SYSTEM MANAGING THE DIGITAL FIRM - Laudon, Kenneth C.; Laudon, Jane P. (Pearson Education Limited, 2022)
Management Information Systems: Managing the Digital Firm provides the most comprehensive overviewof information systems used by business firms today, while drawing connectionsbetween MIS and business performance. The Laudons are known for theiroutstanding real-world case studies, which describe how well-known companiesuse IT to solve problems and achieve business objectives. Students developsought-after skills, such as leading IS-related management discussions andusing IT to meet bottom-line results. Each chapter of the 17th edition featuresall-new Interactive Sessions, new Video Cases, and a new Career Opportunitiessection building practical job-seeking skills.